Être ou ne plus être à sa place au PSG ? Analyse des stratégies des indépendants de la tribune Boulogne du stade du Parc des Princes (Paris) - Gaël Rannou (Territoire en Mouvement)
Before 2010, the supporters named as "independent" of the Paris-Saint-Germain football club had territorialized the Boulogne stand of the Parc des Princes stadium in Paris. In 2010, after the death of a supporter during a brawl, the president of the club took the decision to geographically disperse these independent supporters, preventing their regrouping in the stadium and reconsider their territorialization dynamics. Different fan attitudes and strategies resulted from this institutional decision. By studying in insider and in a micro-geographic approach the practices of these independents of PSG, this article questions the possibility for these supporters to continue to exist as such without territory.